2020
DOI: 10.1503/cmaj.190385
|View full text |Cite
|
Sign up to set email alerts
|

Association between household food insecurity and mortality in Canada: a population-based retrospective cohort study

Abstract: F ood insecurity-inadequate access to food because of financial constraints-is a public health concern in Can ada. 1,2 In 2007/08, 11.3% of households experienced food insecurity; the figure rose to 12.4% by 2011/12. 1,2 Food insecurity is associated with negative health outcomes and higher health care spending in a graded fashion, with more severe food insecur ity corresponding to worse health and greater health care utiliza tion. 3-5 Food insecurity predicts higher incidence of chronic condi tions and poorer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 48 publications
5
86
0
3
Order By: Relevance
“…Our findings also raise the question of the causal mechanism underpinning the elevated mortality observed among severely food-insecure adults of preretirement age. Seniors and non-seniors have been clustered together in past research linking food insecurity to vital status [24][25][26]. Our exploratory analyses found that severely food-insecure adults from our sample were more likely than their food-secure counterparts to die from infectious-parasitic disease, unintentional injuries and suicides although chronic conditions claimed the great majority of pre-65 deaths irrespective of one's food insecurity status (results not shown due to limited death tolls).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Our findings also raise the question of the causal mechanism underpinning the elevated mortality observed among severely food-insecure adults of preretirement age. Seniors and non-seniors have been clustered together in past research linking food insecurity to vital status [24][25][26]. Our exploratory analyses found that severely food-insecure adults from our sample were more likely than their food-secure counterparts to die from infectious-parasitic disease, unintentional injuries and suicides although chronic conditions claimed the great majority of pre-65 deaths irrespective of one's food insecurity status (results not shown due to limited death tolls).…”
Section: Discussionmentioning
confidence: 60%
“…Low income is a strong predictor of food insecurity, yet the two factors capture substantially different aspects of economic hardship with limited overlap [34,35]. Past research on food insecurity and mortality has not stratified the samples by income [24][25][26]. Our stratification yielded a significant association between food insecurity and pre-65 mortality among low-income adults.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations